Alienation And Reconciliation In Amish Tripathi’s The Immortals Of Meluha - N. Navaneetham; Dr. C. Arun (Revista Electronica de Veterinaria, 2024)
This paper explores Amish Tripathi’s debut novel, The Immortals of Meluha (2010), which addresses diasporic themes of alienation and reconciliation. Tripathi, a contemporary Indian English writer, draws inspiration from the Shiva Purana, reimagining the legendary Shiva in a human form as the protagonist of his Shiva Trilogy. Here, Tripathi presents Shiva as a mortal, a leader of the Guna tribe from Lake Mansarovar, at the base of Mount Kailash in Tibet, who migrates to the ancient city of Meluha.  Shiva’s journey includes transformation into the “Neelkanth” after consuming the mystical drink Somras.  In Meluha, he experiences a mixture of nostalgia, alienation, and eventual reconciliation with his new environment.  While previous studies have analyzed various aspects of this novel, few have explored the diasporic elements it presents through Shiva’s perspective as a refugee.